Dialogue implication in Naguib Mahfouz's plays, a Gharaisi approach - Jabbar, Ass.Prof PhD. Raed Majeed (Thi Qar Arts Journal, 2022)
The importance of the deliberative lesson lies in analyzing the discourse by interrogating the texts and demonstrating the effectiveness of the communicative operator and the effectiveness of dialogues. Likewise, the starting point from which Paul Grace set out was to stand at the verbal intents and to clarify the difference between what is said and what is intended, i.e. the distinction between what words and phrases mean with their verbal connotations and what is behind those verbal values of intentions that the speaker wants to convey to the listener through arbitration of customary usage standards and inference tools , the idea of implication arose. Therefore, this research paper changes the analysis of dialogue in the plays of Naguib Mahfouz, a therapeutic analysis through the effectiveness of the dialogic imperatives that arise in the dialogues of the characters, as the phenomenon of dialogic imperative is one of the most prominent phenomena that characterizes natural languages, and one of the most important deliberative theories. The importance of this research is also evident in that it takes language as a tool for communication and control in understanding and absorbing the purposes of indirect speech, with an indication of the ability of dialogue in Naguib Mahfouz's plays to embody the mechanisms of implicit communication